Evolution of an Endemic Methicillin-Resistant Staphylococcus aureus Population in an Australian Hospital from 1967 to 1996 - Givney, Rodney (American Society for Microbiology, 1998)
The evolution over 30 years of a population of methicillin-resistant Staphylococcus aureus (MRSA) from a tertiary referral hospital was studied by phylogenetic analysis of SmaI-generated restriction fragment length polymorphisms (RFLPs). The results suggest that a new clone of MRSA appeared at the hospital in the early 1980s, which, although usually retaining its ancestral phage-type, developed four different RFLP pulsotypes in the next 16 years. This finding indicates that multiple RFLP patterns in MRSA do not necessarily represent multiple clones deriving from different mec gene transfer events. Such variation within a clone may be significant in the interpretation of RFLP patterns during outbreaks and emphasizes the need to use two typing methods in studies of such populations. Since the appearance of new clones of MRSA is a relatively rare event, cross-infection control is paramount in the prevention of MRSA dissemination.